Generation Z Perception of Employer Attractiveness: A Survey Study in Bangkok, Thailand - Parvin, Younes (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Without the right employees, companies cannot operate effectively or efficiently. Employer Branding is a tool used for companies to build a brand for themselves as a place to work for, and Employer Attractiveness is the benefits shown that a potential employee will receive for that company. Although proven as useful, our knowledge of Employer Attractiveness has been insufficient globally and practically nonexistent in Thailand, especially when it comes to the study of a generational perspective. This study aims to investigate the factors, which consist of Application Value, Development Value, Economic Value, Reputation Value, Social Value, Work Diversity Value, and Working Environment influencing Employer Attractiveness for Generation Z in Bangkok, Thailand, the demographic factors’ influence is tested as well. 407 responses were collected from online questionnaires distributed through convenience sampling to be analyzed using Multiple Linear Regression, ANOVA, and Independent Sample T-Test to test the hypotheses. Working Environment, Economics Value, Application Value, and Social Value, respectively have a significant influence on Employer Attractiveness for Generation Z in Bangkok, Thailand. Further study is done on the components of each of these factors.